Plataformas modernizadoras en el periodo de José Luis Bustamante y Rivero (1945-1948): revistas y proyectos intelectuales en una Lima democrática - Zarria Ibarra, Zandor Emerson (2019)
The research seeks to review some of the most important modernizing platforms that, through their own mechanisms of cultural production, sought to renew the civic, literary and artistic imaginary of the city of Lima, corresponding to the democratic period of José Luis Bustamante y Rivero (1945-1948 ). In the first place, we developed some ideas about the cultural historical context of Lima at the time mentioned, in addition to locating the ideological coordinates in which some relevant intellectuals are located. Secondly, we propose a definition of the concept ‘modernizing platform’. Finally, we propose to explain the objectives and development of the following modernizing platforms or intellectual projects of the time: Las Moradas magazine (1947-1949), the Espacio group, la Peña Pancho Fierro (1936-1967), and the magazines El Correo de Ultramar (1947) and Mar del Sur (1948-1953).